Determinants of anemia among patients receiving cancer chemotherapy in Northwest Ethiopia - Wondm, Samuel Agegnew; Dagnew, Samuel Berihun; Gubae, Kale; Tesfaye, Tegenu Chanie; Tamene, Fasil Bayafers (Frontiers in Medicine, 2024)
Background: Chemotherapy-induced anemia (CIA) is a hematologic complication that frequently affects patients with cancer undergoing chemotherapy. It is associated with worse treatment outcomes, higher rates of morbidity and mortality, worse quality of life, and higher healthcare costs. The incidence and predictors of CIA in Ethiopia, particularly in Northwest Ethiopian oncology centers, are poorly understood. This study was conducted at Northwest Ethiopian oncology centers to evaluate the incidence and determinants of chemotherapy-induced anemia in adult patients with cancer undergoing chemotherapy.Methods: This 3-year hospital-based retrospective follow-up study included adult patients with cancer receiving chemotherapy between 2019 and 2021 at two oncology centers in Northwest Ethiopia. Data were collected from October to December 2021. A binary logistic regression model was used to select variables and determine the Crude Odds Ratio (COR). Variables with P value <0.2 were entered into the multivariable logistic regression and Adjusted odds ratio (AOR) with 95% Confidence intervals (CI) for variables with P-value <0.05 were estimated to show determinants of chemotherapy-induced anemia among cancer patients who received chemotherapy.Results: A total of 402 patients were included in the final analysis. The overall incidence of CIA was 75.4 % (95% CI 70.7,79.8). Older age [AOR=1.8,95% CI (1.4-3.5); P= 0.043], hematologic cancer [AOR =3.7,95% CI (3.2-5.7), P= 0.021], obesity [AOR=3.4,95% CI (2.3-6.9); P= 0.028], ≥6 chemotherapy cycles [AOR=3.8,95%CI (3.2-5.1), P=0.019], cancer metastasis to bone [AOR=2.9,95% CI (1.2-4.7), P=0.025] were statistically significant predictors of chemotherapy-induced anemia.Chemotherapy-induced anemia persisted in a significant percentage of cancer patients. Chemotherapyinduced anemia developed in three-quarters of patients undergoing chemotherapy. Chemotherapy-induced anemia was significantly associated with older age, hematologic malignancy, obesity, a greater number of chemotherapy cycles, and cancer metastasis to bone. To lower the risk of morbidity related to anemia, patients with chemotherapyinduced anemia should be regularly evaluated and treated with appropriate treatment..